Iraq : A Multi-country South-South Knowledge Exchange on Social Safety Nets - Alkhoja, Ghassan (World Bank, Washington, DC, 2013)
South-South knowledge exchanges are increasingly recognized as one of the most effective learning and development tools. While it is important to facilitate such exchange of first-hand experiences and lessons across developing countries, what is even more important is what is actually done with the outcomes of the learning and knowledge sharing that take place across boundaries. So in this Quick Note authors would like to take it a step further and share the Iraq country experience, which has recently benefitted from South-South knowledge exchange facilitated by the World Bank. In this case, the World Bank not only acted as a facilitator and convener, but also as a solution provider. The cash-based social safety net program administered by the Ministry of labor and social affairs has expanded to reach nearly one million families (based on categorical targeting), with a budget of about US$800 million. Overall, Iraq spends close to 10 percent of its gross domestic product on social safety net programs, of which 7.7 percent is spent on food and fuel subsidies.